Faculty Development for Underrepresented Minority Dental Faculty and Residents. Issue 3 (1st March 2013) - Gates, Paul; Ubu, Ngozi; Smithey, Leslie; Rogers, Jennifer; Haden, N. Karl; Rodriguez, Tobias; Albino, Judith E.N.; Evans, Clyde; Zarkowski, Pamela; Weinstein, George; Hendricson, William D.
Abstract : This report describes the implementation and evaluation of the Bronx‐Lebanon Hospital Center Dental Faculty Development Program (DFDP) for fifteen participants: five advanced dental education faculty members and ten residents. The 100‐hour DFDP, designed in the longitudinal immersion model for faculty development, was conducted in four phases at the Bronx‐Lebanon Department of Dentistry in the Bronx, New York, in 2010–11. The DFDP was implemented to help underrepresented minority (URM) dental residents and clinical faculty members develop skills necessary for academic careers and enhanced teaching effectiveness. The program's curriculum had four themes: teaching and learning, scholarship, academic leadership, and career planning. For each phase, the participants completed pre‐ and post‐training assessments of their knowledge, attitudes, and confidence, as well as qualitative evaluation of DFDP organization, content, activities, and value. The participants' pre‐instruction mean knowledge score for all phases combined was 48.3 percent, and the post‐test score was 81.1 percent (p=0.01). The participants showed minimal change in their attitudes about educational issues, but they reported enhanced confidence for twenty‐five skills addressed in the DFDP. The total confidence score was 77.5 (25 skills × 3.1 group mean) on all pre‐tests combined and 100.2 (25 × 4.0 group mean) on the post‐tests (p=0.01). The participant ratings for overall DFDP implementation and for twenty‐four topical sessions were uniformly positive. The faculty and resident participants in this year‐long faculty development initiative at an advanced dental education program with a high URM representation demonstrated enhanced knowledge and confidence and provided positive program evaluations. This report also describes curricular and assessment enhancements for subsequent years of the DFDP based on the first‐year outcomes.